ANALYSIS OF L-Asparaginase II ENZYME ACTIVITY FROM NATIVE AND RECOMBINANT Escherichia coli DH10B FOR THE APPLICATION OF ACUTE LYMPHOBLASTIC LEUKAEMIA THERAPY - Keysha Putri Febiona; Dian Pertiwi; Arni Amir; Lily Syukriani; Dessy Arisanty; Almurdi Almurdi; Lisana Shiddiqin Aliya; Jamsari Jamsari (BRIN - Badan Riset dan Inovasi Nasional, 2026)
Acute Lymphoblastic Leukemia (ALL) is a blood cancer that occurs due to abnormal proliferation of lymphoid progenitor cells. L-asparaginase II is an enzyme used to treat this disease by inducing apoptosis in cancer cells encoded by the AnsB gene. Previous studies have shown complications and toxicity in commercial L-asparaginase, necessitating exploration of L-asparaginase sources. Serratia plymuthica UBCF_13 is one of the microorganisms that encodes the AnsB gene. This study consisted of inoculation of native E. coli DH10B and E. coli DH10B pET28a(+)_AnsB, molecular validation, enzyme activity testing using direct nesslerisation method, and analysis of extracellular and intracellular protein profiles using SDS-PAGE. Enzyme activity and protein profiles were compared with S. plymuthica UBCF_13, and Isopropyl β-D-1-thiogalactopyranoside (IPTG) induction was performed on each bacteria as a comparison. The results showed the highest L-asparaginase II enzyme activity in E. coli DH10B pET28a(+)_AnsB induced with IPTG with an average enzyme activity of 0.392 ± 0.017 U/mL. Protein profile analysis using SDS-PAGE supported this finding, showing a thicker 36.5 kDa protein band compared to other bacteria. Statistical testing using One Way ANOVA showed a significant difference in L-asparaginase II enzyme activity in native E. coli DH10B and E. coli DH10B pET28a(+)_AnsB. It can be concluded that there was an increase in activity in recombinant E. coli DH10B compared to its native.